Intelligent energy efficient lighting using RGB light-emitting-diode (LED) - Qaleelullah Bin Mohamed Fahim (2011)
LED technology is growing at an impressively rapid rate and LEDs are beginning to replace other types of light sources, such as incandescent lights, fluorescent lights, halogen lights and even HID. LED technology is being sought after for almost all lighting solutions today. As such, there is high demand for LED based lighting solutions. This project is a lab based research hardware project on designing and implementing an intelligent energy efficient lighting using RGB LEDs. The purpose of this project is to build an advanced LED lighting system using RGB LEDs which is intelligent and can be used to directly replace existing fluorescent tube lights being used widely. The first part of the project is research based in which many different aspects of LEDs and LED based solutions are examined and analyzed. The research includes a literature review of previous research carried out on LEDs, their characteristics, their problems and their uses. The second part of the project constitutes designing and implementing a working prototype.